2022
DOI: 10.1039/d1sc06412f
|View full text |Cite
|
Sign up to set email alerts
|

A carbonyl-rich covalent organic framework as a high-performance cathode material for aqueous rechargeable zinc-ion batteries

Abstract: A covalent organic framework (Tp-PTO-COF) with carbonyl active sites was proposed as a novel cathode material and successfully applied in aqueous rechargeable zinc-ion batteries (ZIBs).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
63
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 83 publications
(73 citation statements)
references
References 50 publications
1
63
0
Order By: Relevance
“…In future work, we will alleviate the partial solubility of these materials by cross-linking or by incorporation into polymeric networks, 55,56,[61][62][63][64] which are common methods to overcome this problem in redox-active organic materials. One of the most exciting features of organic electrode materials is that they can be readily adapted to work with almost any cation, including those such as Na + and Mg 2+ that are more abundant than Li + , [65][66][67] and their redox properties can be optimized by tuning hard-soft acid-base interactions. [68][69][70] Indeed, previous molecular studies have demonstrated that 1,2-diones are promising potential electrode materials for Mg-ion batteries, because the two one-electron waves observed with monovalent cations such as Li + collapse into a single two-electron reduction wave with Mg 2+ cations due to the excellent hard-hard match of the divalent cation and the reduced carbonyl groups.…”
Section: Resultsmentioning
confidence: 99%
“…In future work, we will alleviate the partial solubility of these materials by cross-linking or by incorporation into polymeric networks, 55,56,[61][62][63][64] which are common methods to overcome this problem in redox-active organic materials. One of the most exciting features of organic electrode materials is that they can be readily adapted to work with almost any cation, including those such as Na + and Mg 2+ that are more abundant than Li + , [65][66][67] and their redox properties can be optimized by tuning hard-soft acid-base interactions. [68][69][70] Indeed, previous molecular studies have demonstrated that 1,2-diones are promising potential electrode materials for Mg-ion batteries, because the two one-electron waves observed with monovalent cations such as Li + collapse into a single two-electron reduction wave with Mg 2+ cations due to the excellent hard-hard match of the divalent cation and the reduced carbonyl groups.…”
Section: Resultsmentioning
confidence: 99%
“…[ 3,22,23,44–49,120–130 ] Moreover, the emerging ion‐conducting COFs with excellent ionic conductivity and high cation transfer number can reduce the battery polarization and improve the charging/discharging kinetics of electrodes. [ 131–143 ] The distinctive directional selectivity of ionic conduction in COFs is obviously different from the typical inorganic solid conductors and polymer conductors, so that COFs are suitable for diverse battery applications, including lithium‐ion, [ 144–166 ] lithium–sulfur, [ 167–208 ] sodium‐ion, [ 209–214 ] potassium‐ion, [ 215–219 ] lithium–CO 2 , [ 220–223 ] zinc‐ion, [ 224–230 ] zinc–air batteries, [ 231–234 ] etc. In this section, the traditional classification method of battery types is replaced by the classification according to the components among the dif...…”
Section: Applications Of Ion‐conducting Cof In Rechargeable Batteriesmentioning
confidence: 99%
“…[24][25][26][27][28][29][30][31] It is well-known that the high surface area is conductive to embed Li + ions into deep pore sites and enhance their shuttle velocity in the pore. 32,33 Besides, COFs also exhibit better stability than traditional organic materials and hardly dissolve in most solvents. 34 Zhao et al 35 explored the few-layer TP-COF in LIBs by using mechanical exfoliation, where the asexfoliated TP-COF could enable the reversible reaction of Li + with C═N and C═O, and deliver a high initial capacity of 110 mAh/g.…”
Section: Introductionmentioning
confidence: 99%